Membrane characterization based on PEG rejection and CFD analysis - C. Baldasso (2015)
Characterization of membrane pore size by experimental methods is usually done by the determination of the rejection of polymeric molecules having a range of sizes such as PEG. These experiments are affected by concentration polarization, which can lead to erroneous interpretation of the results, mainly because the concentration and the permeate flux change along the membrane surface. Additionally, experimental methods alone are insufficient to obtain the membrane pore size. To improve the current approach, numerical methods are used to understand mass transport limitations in rejection experiments and to predict the membrane pore size. In the current study, the results show that the ultrafiltration membrane has a MWCO of 20 kDa, different from the value set by the manufacturer (30 kDa). For the experimental conditions, concentration dependent viscosity and osmotic pressure do not influence the permeate flow rate or rejection. Moreover, the membrane pore size was found to be 2.59 nm. This value was determined comparing rejection values obtained by numerical and experimental results. Numerical analysis is also important to characterize the flow and mass transport in each point at membrane surface.